Linking Literature, Information, and Knowledge for Biology Workshop of the BioLink Special Interest Group, ISMB/ECCB 2009, Stockholm, June 28-29, 2009, Revised Selected Papers - Blaschke, Christian; Shatkay, Hagit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume of Lecture Notes in Bioinformatics contains selected papers from the workshop of the BioLINK Special Interest Group (SIG) on Linking Literature, Information and Knowledge for Biology. The workshop was held June 28- 29, 2009 at the ISMB/ECCB 2009 conference in Stockholm.
BioLINK 2009 -- Overview of the Ninth Annual Meeting of the BioLINK SIG at ISMB: Linking Literature, Information and Knowledge for Biology -- Principles of Bioimage Informatics: Focus on Machine Learning of Cell Patterns -- Summary of the BioLINK Special Interest Group Session on the Future of Scientific Publishing -- Structured Literature Image Finder: Extracting Information from Text and Images in Biomedical Literature -- Toward Computer-Assisted Text Curation: Classification Is Easy (Choosing Training Data Can Be Hard...) -- Mining Protein-Protein Interactions from GeneRIFs with OpenDMAP -- Combining Semantic Relations and DNA Microarray Data for Novel Hypotheses Generation -- Learning from Positive and Unlabeled Documents for Retrieval of Bacterial Protein-Protein Interaction Literature -- Extracting and Normalizing Gene/Protein Mentions with the Flexible and Trainable Moara Java Library.
Keywords: Computer science; Computer software; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Bioinformatics; Computer Science; Data Mining and Knowledge Discovery; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Pattern Recognition; Image Processing and Computer Vision; Computational Biology/Bioinformatics.